A brief review on recent development of carbon nanotubes by chemical vapor deposition - S. A. Razak; N. N. Nordin; M. A. Sulaiman; M. Yusoff; M. N. Masri (Universiti Malaysia Kelantan, 2016)
Development of carbon nanotubes was done by several methods like arc discharge, laser ablation, silane solution, flame synthesis method but the standard or famous technique using chemical vapor deposition (CVD). CVD is one of the approaches to develop CNT, due to easy control of the reaction course and high purity of the obtained materials. Various type of CVD present like thermal CVD, plasma enhanced CVD, or microwave plasma CVD. These kinds of types give the different advantage and drawbacks to the production of CNT and its preparations.